METAFORA DALAM AL-QUR'AN (Studi Analisis Tasybih, Majaz dan Kinayah dalam Surah al-Mulk ayat 7-8 dan 22) - Affandi, Abdullah (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2023)
Balaghah is the delivery of a message using fluency, between the pronunciation and the intended content of the sentence. By still paying attention to the conditions of disclosure, maintaining the interests of the recipient of the message, and having influence on those who receive the message. The essence of the existence of the science of balaghoh is a study that contains theories related to how to convey expressions that have the value of the balaghoh itself. Balaghoh science is also a tool to understand someone to the knowledge of the I'jaz-an al-Qur'an. In this case, the science of balaghoh is very important, is to lead us to learn about this knowledge so that we can understand the contents of the Al-Quran. This simple article attempts to analyze metaphorically several verses of the Qur'an, namely surah al-Mulk verses 7-8 and 22. Keywords: Metaphoris, balaghah, al-Qur'an